(untitled) (KULT_online, 2015)
Typology as interaction of the Old and the New Testament is a major tradition of Christian iconography. While typological cycles were considered as prevailing in medieval visual culture, Alexander Linke’s doctoral study sheds light on the variety of forms and argumentation of typology in early modern art. It focuses on monumental typological cycles by artists like Michelangelo, Tintoretto, and Rubens.